Farm to Institution to Farm: Circular Food Systems With Native Entomoculture - Shafer, Patrick J.; Chen, Yolanda H.; Reynolds, Travis; von Wettberg, Eric J. B. (Frontiers in Sustainable Food Systems, 2022)
Edible insects recycle food waste, which can help feed a hungrier planet by making food systems more circular and diversifying protein production. The potential for entomophagy (i.e., insect cuisine) to contribute to waste recycling and lower input food production is only beginning to be explored in the U.S., although insects have been consumed by people for millennia in a wide range of cultures. In this perspective piece, we consider as a case study the potential for university foodservice programs in New England to serve as incubators for circular entomophagous food systems. Students are likely early adopters of entomophagy because they increasingly demand sustainable non-meat protein options. University foodservices meanwhile purchase large amounts of food wholesale from local producers, utilize standardized pre-processing, and generate consistent waste streams which may be valuable feed for local insect farmers. Current Farm to Institution approaches strengthen regional food systems by connecting small farmers with university foodservices; we argue that a similar model (Farm to Institution to Farm) could support establishment of local insect farms, introduce edible insects to a relatively receptive base of university student customers, and provide a more sustainable mechanism for repurposing university food waste as insect feed. But to enable this type of food system, additional requirements include: (1) research on domestication of native insect species; (2) investment in processing capacity, ensuring new insect farmers have reliable markets for raw insect products; (3) infrastructure to recirculate waste streams within existing food systems; and (4) creation of recipes that entice new insect consumers.